2006
DOI: 10.1088/0268-1242/22/2/002
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence study and structural characterization of p-type ZnO doped by N and/or As acceptors

Abstract: ZnO doped with N and/or As layers was fabricated by thermal oxidation of ZnTe films grown by MBE on different substrates. Hall effect measurements demonstrated p-type conductivity with a hole concentration of ∼5 × 10 19 cm −3 for ZnO:As and ZnO:As:N on GaAs substrates and ∼6 × 10 17 cm −3 for ZnO:N on ZnTe substrates. The concentration of N and As atoms in ZnO is estimated to be ∼10 20 cm −3 . This suggested that simple substitutional N atoms form acceptor impurities with a smaller efficiency than an As-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 23 publications
3
33
1
Order By: Relevance
“…Quite frequently, this band is observed after www.pss-b.com intentional p-type doping with group V elements like nitrogen [4,5], phosphorous [6][7][8], antimony [9], and arsenic [10]. Expecting that the new PL bands observed after doping must be directly related to the substitutional dopant species, most authors label the 3.31 eV peak as an acceptor bound exciton (A 0 ,X) or as a donor-acceptor pair transition.…”
Section: Experimental and Resultsmentioning
confidence: 99%
“…Quite frequently, this band is observed after www.pss-b.com intentional p-type doping with group V elements like nitrogen [4,5], phosphorous [6][7][8], antimony [9], and arsenic [10]. Expecting that the new PL bands observed after doping must be directly related to the substitutional dopant species, most authors label the 3.31 eV peak as an acceptor bound exciton (A 0 ,X) or as a donor-acceptor pair transition.…”
Section: Experimental and Resultsmentioning
confidence: 99%
“…Next, they were oxidized in a horizontal tube furnace by annealing in an oxygen flow for 2 h at 500 1C. Our annealing time exceeds rapid annealing used for ZnTe films (1-25 min) [35,36] and is comparable to the long annealing (1-5 h) applied toward ZnS [44,45] and Zn x N y [46][47][48] films to assure full transformation of ZnSe into the ZnO. Thickness of ZnSe films was varied between 300 nm and 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, p-type doping utilizing thermal As diffusion from GaAs substrates into the ZnO films [18,21,[30][31][32][33][34] and by oxidation of the ZnTe/GaAs heterostrucutres [35,36] was realized by a number of research groups. In addition, both n-and p-type ZnO films were synthesized through the annealing of undoped ZnSe crystals in the activated oxygen atmosphere (radical beam gettering epitaxy) [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to ZnO, ZnTe can be obtained as a highly p-type doped material. Moreover, it was already shown that thermal oxidation of nitrogen-doped ZnTe allows to obtain p-type ZnO [3]. Up till now the fabrication of ZnTe/ZnO core/shell NW structures was realized by a * corresponding author; e-mail: kgas@ifpan.edu.pl combination of two different growth methods.…”
Section: Introductionmentioning
confidence: 99%